Study of Politeness Strategy of Speech Act Caring Utterances: Discourse Completion Test (DCT) Approach - Susanti, Ratna; Sumarlam, Sumarlam; Djatmika, Djatmika; Rohmadi, Muhammad (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study focuses on exploring utterances of caring in academic interaction between vocational students and between lecturers (s) -students' major in automotive and pharmacy of Polytechnic Indonesia Surakarta. This study analyses two objectives: (1) politeness strategies in expressing warnings, and (2) warning speech sentences carried out by vocational education students. Data was collected using a questionnaire technique in the form of Discourse Completion Test (DCT) which were given to respondents. The five active male and female lecturers were chosen as research subjects. The lecturers teach five different courses. The other participants were 128 students taught by the selected five lecturers.